The new frontiersmen. Profiles of the men around Kennedy. With a forew. by I.W. Hill and an introd. by M.B. Schnapper. [With contribs. by E.H. Voss, L.M. Cohen, R. Fryklund, a.o.] (Public Affairs Press, 1961)
With indices.